OUR EXPIRIENCE WITH INVASIVE SKIN CARCINOMA OF THE SKULL TREATED WITH A ROTATIONAL FLAP - Tomevska, Ana; Mikjunovikj, Mikjun; Bitrakov, Zoran; Trajanoska, Biljana; Ivanoski, Slavco; Radeska, Ana Trimoska; Mikjunovikj, Emilija; Dodevski, Ace (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
The escalating incidence of skin malignancies, particularly in sun-exposed areas such as the head and neck, requires innovative approaches for challenging cases. Squamous cell carcinoma, though common, rarely infiltrates the skull, presenting unique challenges in treatment and reconstruction. In this case report, we describe the management of a 77-year-old patient with recurrent invasive squamous cell carcinoma of the left temporal region extending into the skull. The patient underwent three surgeries within our institution due to squamous cell carcinoma recurrence, leading to a complex skin defect unsuitable for conventional closure methods. Our approach involved the use of a local rotational flap, using the robust vascularity of the scalp, allowing versatile orientation relative to the defect. The operating technique consisted of a craniectomy, removal of infiltrated tissue, and affected dura, followed by plastic reconstruction of the skin with a rotational flap, preserving healthy periosteum and temporal fascia. As the population with cutaneous neoplasms ages, the demand for expeditious and less morbid reconstructive options grows. This case underlines the effectiveness of the local rotational flap for reconstructing medium-sized complex scalp defects post-cancer resection. Our experience suggests that the rotational scalp flap is a reliable and safe choice, offering a favorable balance between surgical outcomes and patient well-being.   Keywords: scalp, squamous cell carcinoma, rotation advancement flap, recurrence, invasion of dura.